Direct comparison of diagnostic performance of 9 quantitative fecal immunochemical tests for colorectal cancer screening - Gies, Anton; Cuk, Katarina; Schrotz-King, Petra; Brenner, Hermann (Gastroenterology, 2018)
BACKGROUND & AIMS: A variety of fecal immunochemical tests (FITs) for hemoglobin (Hb) are used in colorectal cancer screening. It is unclear to what extent differences in reported sensitivities and specificities reflect true heterogeneity in test performance or differences in study populations or varying pre-analytical conditions. We directly compared the sensitivity and specificity values with which 9 quantitative (laboratory-based and point-of-care) FITs detected advanced neoplasms (AN) in a single colorectal cancer screening study. METHODS: Pre-colonoscopy stool samples were obtained from participants of screening colonoscopy in Germany from 2005 through 2010 and frozen at -80°C until analysis. The stool samples were thawed, homogenized, and used for 9 different quantitative FITs in parallel. Colonoscopy and histology reports were collected from all participants and evaluated by 2 independent, trained research assistants who were blinded to the test results. Comparative evaluations of diagnostic performance for AN were made at preset manufacturers' thresholds (range, 2.0-17.0 μg Hb/g feces), at a uniform threshold (15 μg Hb/g feces), and at adjusted thresholds yielding defined levels of specificity (99%, 97%, and 93%). RESULTS: Of the 1667 participants who fulfilled the inclusion criteria, all cases with AN (n = 216) and 300 randomly selected individuals without AN were included in the analysis. Sensitivities and specificities for AN varied widely when we used the preset thresholds (21.8%-46.3% and 85.7%-97.7%, respectively) or the uniform threshold (16.2%-34.3% and 94.0%-98.0%, respectively). Adjusting thresholds to yield a specificity of 99%, 97%, or 93% resulted in almost equal sensitivities for detection of AN (14.4%-18.5%, 21.3%-23.6%, and 30.1%-35.2%, respectively) and almost equal positivity rates (2.8%-3.4%, 5.8%-6.1%, and 10.1%-10.9%, respectively). CONCLUSIONS: Apparent heterogeneity in diagnostic performance of quantitative FITs can be overcome to a large extent by adjusting thresholds to yield defined levels of specificity or positivity rates. Rather than simply using thresholds recommended by the manufacturer, screening programs should choose thresholds based on intended levels of specificity and manageable positivity rates.
Gesehen am 25.01.2018
Article was first available online on 25 September 2017